Glacier-Related Hazards Along the International Karakoram Highway: Status and Future Perspectives - Gao, Yongpeng; Liu, Shiyin; Qi, Miaomiao; Xie, Fuming; Wu, Kunpeng; Zhu, Yu (Frontiers in Earth Science, 2021)
The China–Pakistan international Karakoram Highway passes through the core area of the ‘Karakoram Anomaly’, whose glaciers have maintained or increased their mass during a period when most glaciers worldwide have receded. We synthesized the literature and used remote-sensing techniques to review the types, distribution, characteristics, causes and frequency of major glacial hazards along the Karakoram Highway. We found that the glacier-related hazards could be divided into direct and indirect hazards, including glacier surges, glacial lake outburst floods, and glacial floods, which are concentrated in East Pamir and the Hunza River Basin. In the past 100 years, hazards from glaciers surges and glacial floods only occurred once and twice, respectively, which appear suddenly, with the hazard-causing process being short-lived and occurring mainly in the summer. Glacial lake outburst floods mainly occur in the spring and summer in the Hunza River Basin. Among these, ice-dammed lakes have the highest frequency of flooding, their formation and outbursts being closely related to the sudden advancement of surge-type glaciers. The glacier surge cycle, and thus the occurrence frequency of related hazards, may shorten under continued climate warming. Similarly, global warming will accelerate the melting of glaciers in the future, which will increase frequency of the formation and outbursts in the glacial lakes. In the future, we should combine models and new field observations to simulate, and deepen our understanding of the physical mechanisms of different glacier-related hazards. In particular, on-site monitoring should be carried out, to include the evolution of glaciers subglacial hydrological systems, the thermal state at the base of the glaciers, and the opening and closing of drainage channels at the base of the ice dams.